Crowdcasting: Remotely Participating in Live Events Through Multiple Live Streams - Tang, John; Venolia, Gina; Inkpen, Kori; Parker, Charles; Gruen, Robert; Edelman Pelton, Alicia (Proceedings of the ACM on Human-Computer Interaction, 2017)
We designed and developed a “crowdcasting” prototype to enable remote people to participate in a live event through a collection of live streams coming from the event. Viewers could select from a choice of streams and interact with the streamer and other viewers through text comments and heart reactions. We deployed the prototype in three live events: a Winterfest holiday festival, a local Women’s March, and the South by Southwest festival. We found that viewers actively switched among a choice of streams from the event and actively interacted with each other, especially through text comments. Streams of walking about among exhibits or city sights elicited more user interaction than streams of lectures. We observed that voluntary viewers had a wider variation in how long they viewed the event, and switched among streams less and had less interaction through text comments compared to viewers recruited through Mechanical Turk.